Through a Feminist Lens: What Do Feminist Online Spaces Look Like During a Pandemic? - Laguilles-Timog, Rowena A.; Cruz, Maritess D. (Review of Women's Studies, 2023)
This feminist research sought to describe feminist online spaces during the COVID-19 pandemic in the Philippines based on the experiences of six feminist organizations. Central to its methodology is the online multimedia storyboarding, a customized method which involves the use of online tools such as a video conferencing application and an online collaborative bulletin board. The following themes were surfaced from the organizations' experiences with creating and maintaining feminist online spaces: motivating situations, activities for internal members of the organization, activities for the larger community or the public, people with access to the spaces, underlying values, and ongoing concerns. From these, two models were formulated. The process model captured the development of feminist online spaces at the start of the pandemic, one year into the pandemic, and in the near future - both in terms of the organization's operations as well as the scope of their community of concern. The conceptual model proposes that feminist online spaces during the COVID-19 pandemic are an integration of responses to gender issues brought about by the pandemic, the increasing power of the Internet at a time of physical mobility restrictions, and the decreasing boundaries between offline and online spaces. This study highlights the role of feminist online spaces in social transformation during the pandemic and beyond, and the need for a stronger appreciation for them from feminist organizations, the development sector, and policymakers in the government.